2015
DOI: 10.1007/s10706-015-9885-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Characteristics of Floating Piles Under Rotating Machine Induced Vertical Vibration

Abstract: This study presents a finite element based approach to evaluate the linear and nonlinear frequency-amplitude response of floating piles subject to rotating machine induced vertical vibrations. A Matlab program is developed to compute the response of a single pile with floating tip condition for a linear and two nonlinear soil models. The variation of complex soil stiffness parameters with frequency has also been presented using different boundary zone parameters (shear modulus reduction ratio, thickness ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To ascertain the dynamic nonlinear horizontal and rocking responses of the soil-pile model after incorporating boundary zones in the continuum technique, theoretical analysis has therefore been carried out in the current inquiry with the aid of an analogous linear soil model. Since the mechanism involved in predicting an accurate boundary zone is difficult in the absence of test or laboratory results because of the insufficient guidelines, As a result, a trial-and-error method is used to forecast these zone characteristics based on the ranges offered by other researchers (Elkasabgy and El Naggar 2013;Sinha et al 2015;Han and Novak 1988;Vaziri and Han 1992). The values of soil characteristics in the border zone are modified for different excitation intensities until the best agreement between the experimental and numerical data is obtained.…”
Section: Boundary Zone Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To ascertain the dynamic nonlinear horizontal and rocking responses of the soil-pile model after incorporating boundary zones in the continuum technique, theoretical analysis has therefore been carried out in the current inquiry with the aid of an analogous linear soil model. Since the mechanism involved in predicting an accurate boundary zone is difficult in the absence of test or laboratory results because of the insufficient guidelines, As a result, a trial-and-error method is used to forecast these zone characteristics based on the ranges offered by other researchers (Elkasabgy and El Naggar 2013;Sinha et al 2015;Han and Novak 1988;Vaziri and Han 1992). The values of soil characteristics in the border zone are modified for different excitation intensities until the best agreement between the experimental and numerical data is obtained.…”
Section: Boundary Zone Parametersmentioning
confidence: 99%
“…Similar types of experiments were done by Burr et al (1997) on various small-scale soil-pile setups in varying soil layers to study the influence of soil-pile spacing to diameter ratio on the nonlinear response of piles. Further, these dynamic results are studied under harmonic vibration and analytically with the use of the continuum approach method by Elkasabgy and El Naggar (2013) and Sinha et al (2015) to know the effect on soil nonlinearity subjected to dynamic excitation and the combined soil-pile responses in terms of frequency and amplitude and their influence on impedance parameters. Some other researchers (Elkasabgy and Naggar 2018;Biswas and Manna 2018;Ralli et al 2022;Kumar et al 2022) also worked in this area and did experimental field and laboratory tests on different setups and compared their datasets with the theoretical curves measured from the continuum approach.…”
Section: Introductionmentioning
confidence: 99%
“…Goit and Saitoh (2013) conducted an experimental test on single fixed head floating piles with the help of a uniaxial shake table and observed that the nonlinearity influences the response of the soil-pile system. Field and laboratory tests are further carried out by some other researchers (Elkasabgy & EI Naggar, 2013;Sinha et al, 2015;Manna, 2018 andChoudhary et al, 2020) who worked in pile dynamics and performed dynamic field tests on piles and compared their results with the nonlinear analytical curves obtained using a continuum approach. It was observed that the analytical results provided a reasonable estimation of dynamic response curves as compared to the field results under machine vibrations.…”
Section: Introductionmentioning
confidence: 99%